Comparative Synthesis and Characterization of Bio-Cellulose from Local Waste and Cheap Resources - Mazhar Ul-Islam (Current Pharmaceutical Design, 2019)
Background: Bacterial cellulose (BC) has been extensively utilized in a wide range of applications specifically in the biomedical field thanks to its excellent physico-chemical and biological features. The major limitation restricting its application in certain areas is its high production cost. Its widespread applications demand exploration of alternative production media compared to the existing expensive ones. Herein, an effort has been made to utilize waste and cheaply available local resources including; waste (expired) orange juice (WOJ), sugarcane juice (SC) and coconut water (CW) as alternative media for BC production in comparison to the synthetic media (control). Methods: Waste and cheap resources were collected from the local market, screened filtered and optimized for the development of BC culture media. BC production from all media was observed under static cultivation for 10 days. The results indicated 2.75, 2.56, 3.32 and 1.68 g/L BC production that corresponded to 27.5%, 21.7 %, 20.1 % and 31.6 % sugar to BC conversion from control, WOJ, SC and CW media, respectively. Morphology and crystalline features of produced BC samples were observed through FE-SEM and XRD analysis. It was noteworthy that BC produced from all alternative sources indicated high water holding capabilities (WHC) and water retention time (WRT) that augment their applicability in drug delivery and wound healing applications. Conclusion: The BC production from cheap resources and its high physical, mechanical and biological properties can be of high interest for scaling up and commercialization of BC production processes. Furthermore, its liquidabsorbing capabilities and retention time can help in drug carrying and medical application.
Keywords: waste sources